Transitioning from Microballs to Microrods Via Time Interval: Shaping Cobalt Vanadium Oxide for Use in Energy Storage Devices - Radhalayam, D (Elsevier B.V., 2025)
Developing self-supported electrode material in the absence of electro-inert binders considering the effortless transfer of charges and manipulating physicochemical properties of electrodes in energy storage devices is essential. This investigation focuses on the facile hydrothermal synthesis of a cobalt vanadium oxide (Co3V2O8) microstructure with tailored properties for supercapacitor application. Morphological change from microballs to microrods is detected in prepared Co3V2O8 microstructure owing to reaction time variation. The synthesized CVO-AFU-7 h electrode material displays superior supercapacitive performance of 318 F/g at 3 mA/cm2 scan rate. Furthermore, the solid-state hybrid supercapacitor (SSHSc) device revealed superior energy storage capabilities, delivering a high energy density of 3.21 Wh/kg at a power density of 169.69 W/kg. The SSHSc device exhibits long lasting cyclability, retaining 79 % of its initial capacity after 10,000 cycles. Moreover, its practical utility is demonstrated by powering three LEDs simultaneously, indicating strong potential for industrial applications. © 2025 Elsevier B.V.